2015
DOI: 10.1016/j.jare.2014.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Non-uniform cosine modulated filter banks using meta-heuristic algorithms in CSD space

Abstract: This paper presents an efficient design of non-uniform cosine modulated filter banks (CMFB) using canonic signed digit (CSD) coefficients. CMFB has got an easy and efficient design approach. Non-uniform decomposition can be easily obtained by merging the appropriate filters of a uniform filter bank. Only the prototype filter needs to be designed and optimized. In this paper, the prototype filter is designed using window method, weighted Chebyshev approximation and weighted constrained least square approximatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Table 1 shows the performance comparison of different nonuniform cosine modulated filter banks using merging method. It is observed that the method proposed in [18] gives minimum amplitude distortion error with minimum filter order.…”
Section: Merging Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Table 1 shows the performance comparison of different nonuniform cosine modulated filter banks using merging method. It is observed that the method proposed in [18] gives minimum amplitude distortion error with minimum filter order.…”
Section: Merging Methodsmentioning
confidence: 95%
“…Initially an NPR uniform CMFB is designed using linear search technique [18]. Only the prototype filter is designed and optimized.…”
Section: Merging Methodsmentioning
confidence: 99%
“…The HSA explores the search space for finding the candidate solutions with good fitness value. The various phases involved in HSA are initialization of harmony memory, harmony improvisation, memory consideration, pitch adjustment, random selection, memory updates and termination [16,39,40]. The weights of the objective function for HSA are obtained as, b 1 ¼ 0:6, b 2 ¼ 2, b 3 ¼ 1 and b 4 ¼ 0:03 by trial and error method, in order to get the desired specifications.…”
Section: Optimization Of Mdft Filter Banks With Pr Using Hsa Algorithmmentioning
confidence: 99%
“…The positions of the masses are updated in each iteration. The various steps involved in GSA are initialization of agents, fitness evaluation, gravitational constant update, acceleration of agents calculation, update the velocity and position of agents and termination [17,39,40]. The weights of the objective function for GSA are obtained as, b 1 ¼ 1, b 2 ¼ 2, b 3 ¼ 1 and b 4 ¼ 0:05 by trial and error method, in order to get the desired specifications.…”
Section: Optimization Of Mdft Filter Banks With Pr Using Gsa Algorithmmentioning
confidence: 99%
“…Therefore, authors have used different optimization algorithms such as differential evolution (DE), harmony search algorithm (HSA), gravitational search algorithm (GSA) for designing multiplier-less M−channel uniform and nonuniform filter banks to enhance the performance by minimizing the errors occurred due to quantization and CSD conversion of filter coefficients [3,13,19]. This was further modified using meta-heuristic algorithms to design frequency response masking (FRM)-based multiplier-less NUFB [2,18]. While in [24,28], a linear search technique and DE algorithm have been used for designing the filter banks, where CSD represented filter coefficients are optimized.…”
Section: Introductionmentioning
confidence: 99%